Elective caesarean section and neonatal outcome: an observational study from a tertiary hospital in Mysore, Karnataka, India - Shivanagappa, Mamatha; Veerabhadrappa, Vinutha K.; Thandaveshwar, Deepthi; Mahesh, Madhumitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Globally 18.6 percent of all births occur by Caesarean Section (CS) and the trend is increasing. In India CS rates have risen from 2.9% in 1992 to 17.2% in 2015. The optimal timing of CS is still being investigated. Data with regard to elective CS and neonatal outcome from India is sparse and this study aimed to obtain the same in the setting of a South Indian Hospital. The objective was to evaluate neonatal outcome and NICU admissions in elective CS Methods: This was a retrospective study conducted at a tertiary care referral hospital and data collected was of deliveries conducted from Jan 2017 to July 2018. All term singleton pregnancies (>37 gestational weeks) scheduled for elective CS were included in the study. Results: A total of 3174 Caesarean Sections were performed during the study period of which 1087 were elective CS and 2087 were done on an emergent basis. Of these elective CS, 425 (39%) were performed at early term (37+0 until 38+6) and 662 (61%) were performed at full term (>39 weeks). Analysis of adverse neonatal outcomes revealed that a significantly higher rate of NICU admission, low birth weight, respiratory complications in newborns delivered at early term than in those delivered at full term. Conclusions: In the present study newborns delivered at 37- 38 weeks of gestation had a higher rate of NICU admission, low birth weight and respiratory complications compared to newborns delivered after 39 weeks of gestation. Neonatal outcome was found to be better in those elective CS done after 39 weeks in comparison to those delivered at early term (< 39 weeks).